UV-triggered p21 degradation facilitates damaged-DNA replication and preserves genomic stability - Mansilla, Sabrina Florencia (2013)
Although many genotoxic treatments upregulate the cyclin kinase inhibitor p21, agents such as UV irradiation trigger p21 degradation. This suggests that p21 blocks a process relevant for the cellular response to UV. Here, we show that forced p21 stabilization after UV strongly impairs damaged-DNA replication, which is associated with permanent deficiencies in the recruitment of DNA polymerases from the Y family involved in translesion DNA synthesis), with the accumulation of DNA damage markers and increased genomic instability. Remarkably, such noxious effects disappear when disrupting the proliferating cell nuclear antigen (PCNA) interacting motif of stable p21, thus suggesting that the release of PCNA from p21 interaction is sufficient to allow the recruitment to PCNA of partners (such as Y polymerases) relevant for the UV response. Expression of degradable p21 only transiently delays early replication events and Y polymerase recruitment after UV irradiation. These temporary defects disappear in a manner that correlates with p21 degradation with no detectable consequences on later replication events or genomic stability. Together, our findings suggest that the biological role of UV-triggered p21 degradation is to prevent replication defects by facilitating the tolerance of UV-induced DNA lesions.